Mobile Interventional Stroke Team Model Improves Early Outcomes in Large Vessel Occlusion Stroke: The NYC MIST Trial. Issue 12 (December 2020) - Morey, Jacob R.; Oxley, Thomas J.; Wei, Daniel; Kellner, Christopher P.; Dangayach, Neha S.; Stein, Laura; Hom, Danny; Wheelwright, Danielle; Rubenstein, Liorah; Skliut, Maryna; Shoirah, Hazem; De Leacy, Reade A.; et al.
Abstract : Background and Purpose: Triage of patients with emergent large vessel occlusion stroke to primary stroke centers followed by transfer to comprehensive stroke centers leads to increased time to endovascular therapy. A Mobile Interventional Stroke Team (MIST) provides an alternative model by transferring a MIST to a Thrombectomy Capable Stroke Center (TSC) to perform endovascular therapy. Our aim is to determine whether the MIST model is more time-efficient and leads to improved clinical outcomes compared with standard drip-and-ship (DS) and mothership models. Methods: This is a prospective observational cohort study with 3-month follow-up between June 2016 and December 2018 at a multicenter health system, consisting of one comprehensive stroke center, 4 TSCs, and several primary stroke centers. A total of 228 of 373 patients received endovascular therapy via 1 of 4 models: mothership with patient presentation to a comprehensive stroke center, DS with patient transfer from primary stroke center or TSC to comprehensive stroke center, MIST with patient presentation to TSC and MIST transfer, or a combination of DS with patient transfer from primary stroke center to TSC and MIST. The prespecified primary end point was initial door-to-recanalization time and secondary end points measured additional time intervals and clinical outcomes at discharge and 3 months. Results: MIST had a faster mean initial door-to-recanalization time than DS by 83 minutes ( P <0.01). MIST and mothership had similar median door-to-recanalization times of 192 minutes and 179 minutes, respectively ( P =0.83). A greater proportion had a complete recovery (National Institutes of Health Stroke Scale of 0 or 1) at discharge in MIST compared with DS (37.9% versus 16.7%; P <0.01). MIST had 52.8% of patients with modified Rankin Scale of ⩽2 at 3 months compared with 38.9% in DS ( P =0.10). Conclusions: MIST led to significantly faster initial door-to-recanalization times compared with DS, which was comparable to mothership. This decrease in time has translated into improved short-term outcomes and a trend towards improved long-term outcomes. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03048292. Abstract : Supplemental Digital Content is available in the text.